Analysis of 783 Cases of Total Laparoscopic Hysterectomy for Benign Indications: Experience from a Turkish University Hospital - Ali Buhur; Omer Unal (IMR Press, 2023)
Background: This study aimed to assess the results of 783 total laparoscopic hysterectomies performed in our clinic for benign reasons. Methods: This study was conducted at a tertiary hospital between January 2017 and December 2020. The results of 783 patients who underwent total laparoscopic hysterectomy for benign indications were evaluated retrospectively, with major and minor complications thoroughly analyzed. Patients' demographic characteristics were evaluated, including mean age, mean parity, body mass index (BMI), current medical diseases, previous surgeries, hysterectomy indications, operation time, uterus weights, estimated blood loss, and length of hospital stay. The ethics committee of Istanbul Kanuni Sultan Süleyman Training and Research Hospital provided the study's ethical approval (Approval No. 2021.11.290). SPSS for Windows 24.0 (SPSS Inc., Chicago, IL, USA) was used for statistical analysis, and data were presented as mean, standard deviation, and ratio, with statistical significance set at p < 0.05. Preoperative and postoperative variables were compared using a paired t-test. Results: For the study's 783 patients, the average age was 50.16 years (range, 33-82), average parity was 3.26 (0-16), and average BMI was 24.37 (21-33) kg/m2. Uterine myoma was the most common reason for hysterectomy in 244 (31.16%) patients, followed by abnormal uterine bleeding in 239 (30.52%) patients. The rate of major complications was 46 (5.8%), and the rate of minor complications was 42 (5.5%). Overall, there were 88 (11.30%) complications. The complication rate and operation indications were comparable to those reported in the literature. Conclusions: Although Laparoscopic hysterectomy is a minimally invasive type of hysterectomy, surgeons should be aware of potential complications during the procedure. Early diagnosis and management of complications reduce morbidity and mortality.